PENGARUH KUALITAS PRODUK DAN KARAKTERISTIK KONSUMEN TERHADAP PEMBELIAN SAYURAN HIDROPONIK (Suatu Survei Terhadap Konsumen Sayuran Hidroponik UPTD Kawasan Agroeduwisata Cikundul Kota Sukabumi) - Widhi Handaya; Euis Dasipah; Karyana KS; Nendah Siti Permana; Dety Sukmawati (Universitas Galuh, 2023)
The research was conducted with the aim of (1) analyzing the effect of product quality and consumer characteristics on the purchase of hydroponic vegetables UPTD Kawasan Agroeduwisata Cikundul; (2) analyzing the effect of product quality on the purchase of hydroponic vegetables UPTD Kawasan Agroeduwisata Cikundul; (3) analyzing the effect of consumer characteristics on the purchase of hydroponic vegetables UPTD Kawasan Agroeduwisata Cikundul. The research method used in this research is a limited survey method to consumers of hydroponic vegetables UPTD Kawasan Agroeduwisata Cikundul. The form of the research is verification research (explanatory). Respondents or research samples were selected using the incidental sampling method. The analysis technique used is descriptive analysis and path analysis to test between variables. The conclusion of the research show that product quality and consumer characteristics together have a real positive influence on the purchase of hydroponic vegetables by 25.7%. Partially, the product quality factor gave a real positive influence on the purchase of hydroponic vegetables by 9% and the consumer characteristics factor gave a real positive influence on the purchase of hydroponic vegetables by 16.7%. Based on the results of this study, it is suggested to the UPTD Kawasan Agroeduwisata Cikundul, Sukabumi City to give more attention to the quality of hydroponic vegetable products to increase purchases.